Effect of carbamide peroxide treatment on the ion release of different dental restorative materials - Merve Nur Yilmaz; Pinar Gul (BMC, 2024)
Abstract Background To predict the long-term performance of restorative materials in the oral environment, it is important to evaluate their resistance to chemical and mechanical degradation and to know the toxic potential of the type and amount of ions eluted from the filling material. In this study, home bleaching was applied to dental materials with different contents and it was aimed to determine the type and amount of ions released from these materials. Methods In this study, amalgam, posterior composite resin, anterior composite resin, bulk fill composite resin, indirect composite resin, hybrid ceramic and all-ceramic were used as restorative materials. 10 specimens of each material were prepared according to the manufacturer's instructions. Each material group was divided into two subgroups as the bleached group and the control group. After bleaching, all specimens were stored in 1 ml of 75% ethanol/water solution. Solutions were renewed after 1, 14 and 28 days. The type and amount of ions released from the materials were determined using Inductively Coupled Plasma-Mass Spectrometer (ICP-MS). Data were analyzed using the Friedman, Wilcoxon Signed Ranks, and Mann-Whitney U tests (α = 0.05). Results It was determined that the amount of ions release from the restorative materials decreased over time (p < 0.05). According to the results of the Mann-Whitney U test, there was no difference between the bleaching and control groups in most of the restorative materials (p > 0.05). Conclusion Within the limits of this study, home bleaching system does not have a significant effect on ion release from restorative materials.